Pressure Ulcers in Covid-19 Patients - Qazi, Mustafa (International Journal of Pathology, 2022)
Background: Pressure ulcers are considered as one of the top five preventable patient safety problems in hospitals. Pressure ulcers are increasingly emerging among hospitalized patients including the COVID-19 patients. The aim of this study was to investigate the frequency of pressure ulcers in COVID-19 patients. Methods: This was a retrospective study conducted at a tertiary care hospital. Data were collected on patient demographics, department, site of pressure ulcer, stage of pressure ulcer and length of stay at the hospital. All patients who acquired pressure ulcers during their stay at the hospital from 1st July 2020 to 30th June 2021 were included in the study. Results: 32 patients were documented to have acquired Pressure Ulcers during their stay at the hospital. 21 (65.6%) of the patients were males and 11 (34.4%) were females. Most Pressure Ulcers were present in adults aged 51 to 70 years. Almost half of the cases were of Grade 1 and 2 Pressure Ulcers while the most common sites were Sacrum and Gluteal region. Conclusion: Patients suffering from COVID-19 as well as their families go through a lot and Pressure Ulcers, which are easily preventable, add to their misery. The concerned patient safety authorities should provide awareness and training to focus on the prevention and early detection of Pressure Ulcers to reduce or entirely eradicate the risk of complications.